2001
DOI: 10.1074/jbc.m007238200
|View full text |Cite
|
Sign up to set email alerts
|

Retention of the Alzheimer's Amyloid Precursor Fragment C99 in the Endoplasmic Reticulum Prevents Formation of Amyloid β-Peptide

Abstract: ␥-Secretase is a membrane-associated endoprotease that catalyzes the final step in the processing of Alzheimer's ␤-amyloid precursor protein (APP), resulting in the release of amyloid ␤-peptide (A␤). The molecular identity of ␥-secretase remains in question, although recent studies have implicated the presenilins, which are membrane-spanning proteins localized predominantly in the endoplasmic reticulum (ER). Based on these observations, we have tested the hypothesis that ␥-secretase cleavage of the membrane-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 113 publications
(141 reference statements)
6
44
1
Order By: Relevance
“…Several lines of data suggest that APP-C99 is processed by ␥-secretase activity mainly at the plasma membrane or in endocytotic compartments, although a major pool of the ␥-secretase complex resides at early secretory compartments (37,38). On the other hand, previous reports (39,40) estimated that only a small portion of the total proteolyzed PS1 fragments in cellular membranes is engaged in active ␥-secretase complexes.…”
Section: Discussionmentioning
confidence: 94%
“…Several lines of data suggest that APP-C99 is processed by ␥-secretase activity mainly at the plasma membrane or in endocytotic compartments, although a major pool of the ␥-secretase complex resides at early secretory compartments (37,38). On the other hand, previous reports (39,40) estimated that only a small portion of the total proteolyzed PS1 fragments in cellular membranes is engaged in active ␥-secretase complexes.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, transgenic mice show accelerated neurodegeneration without extracellular amyloid deposition (24), indicating that intracellular amyloid-␤ peptides may play a crucial role in the development of AD. Intracellular sites with ␥-secretase activity were identified in primary neurons, neuronal cell lines, and peripheral cells (25)(26)(27)(28)(29)(30). Evidence has been obtained for the generation of A␤42 within the ER (27)(28)(29)31), where PS is predominantly localized (14 -16).…”
mentioning
confidence: 92%
“…Evidence has been obtained for the generation of A␤42 within the ER (27)(28)(29)31), where PS is predominantly localized (14 -16). However, it has also been reported that A␤42 is produced in different organelles later in the secretory pathway and that the ER is not the major intracellular site of A␤42 generation (26,30,(32)(33)(34)74). Additionally, recent work has suggested that the A␤42 generation in the ER may be independent of PS (35).…”
mentioning
confidence: 99%
“…The g-secretase subunits found in the ER/early secretory pathway most likely represent unassembled or partially assembled subcomplexes, but not the active enzyme. The evidence supporting such a model is manifold and, because of space constraints, only key arguments will be highlighted: (1) APP/C99/C83 are not cleaved by g-secretase in the ER (Cupers et al 2001;Maltese et al 2001;Grimm et al 2003;Kaether et al 2006b); (2) by immuno-electron microscopy, PS1 is not detected in Golgi or TGN but in ER and PM (Rechards et al 2003); whereas the ER pool most likely reflects unassembled PS1, the PM pool has assembled, active complex; (3) only the mature, glycosylated NCT, not immature unglycosylated NCT, is present in the fully assembled, active g-secretase complex Kaether et al 2002), and therefore g-secretase-associated NCTmust have passed the Golgi; (4) g-secretase has been shown by various methods, including cell surface biotinylation, binding of biotinylated inhibitors specific for the active complex, and microscopic techniques, to be present at the PM (Kaether et al 2002;Tarassishin et al 2004;Chyung et al 2005). It has been shown that the 1-cleavage of APP differs in endosomes and PM (Fukumori et al 2006), suggesting that g-secretase has different properties depending on its subcellular localization, maybe because of differences in pH or lipid composition.…”
Section: Subcellular Sites Of G-secretase-mediated App Processingmentioning
confidence: 99%